Assessment of Coastline Changes Along Lagos West Mole - Hamid-Mosaku, Isa Adekunle; Shittu, Ibrahim Opeyemi; Jimoh, Olalekan Abeeb; Oguntade, Olatoye Fatai; Adekola, Rasidat (International Journal of Marine Engineering Innovation and Research, 2025)
Assessment of coastline changes is crucial to coastal development and management. The Lagos coast is still prone to sediment trap and erosion to date despite the construction of the three moles to solve siltation challenges; moreover, their rates and distributions are yet to be adequately evaluated. This study examines changes along the Lagos West Mole and the possible degree of distributions along the coast between 1984 and 2018 for six epochs. Acquired Landsat imageries were processed to delineate water boundary using Modified NDWI and extract the respective coastlines from the classified waterbodies. Coastline changes were quantified using Digital Shoreline Analysis System (DSAS); the Relative Shannon Entropy (RSE) model was used to measure the degree of concentrations of accretions and/or erosions. Results revealed more profound coastal accretions than erosions; whereas RSE values portrayed dispersed accretions more than erosions. Hence, the outcomes can aid stakeholders’ informed decisions concerning coastal protection and management.